KONTRIBUSI PAJAK DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) DAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) KOTA SEMARANG - Kurnianto Nur Utomo, 09.05.52.0140; Maryono, Maryono (Students Journal of Accounting and Banking, 2014)
This study aims to analyze the growth, contribution, and the effectiveness of local taxes and Retribution to PAD, and APBD in Semarang City Government. The data was collected by the method of documentation. The data used are time series data. The data used are secondary data, obtained from the Department of Finance and Asset Management Area (DPKAD) Semarang. Analysis of the data used is descriptive analysis using growth analysis, contribution analysis, and analysis of effectiveness.These results indicate that the average percentage growth of 61.19% local taxes. The average percentage growth of 10.21% Retribution. The average percentage growth in revenue of 28.91%. Contribution to the regional tax revenue by an average of 5.11%. Retribution contribution to PAD on average by 6.21%. Local Tax Contribution APBD an average of 48.91%. Retribution contribution to the APBD by an average of 1.44%. PAD contribution to the APBD by an average of 24.07%. Local Tax effectiveness with an average of 114.94%. Effectiveness Retribution average of 94.00%. The average percentage of PAD of 110.69% effectiveness. Independence ratio of Semarang categorized independently.Keywords: Local Taxes, Retribution, PAD, APBD